Facial morphology analysis of Caucasian Brazilian adult women using stereophotogrammetry - Maria Gabriela Robles Mengoa; Amanda Aparecida Maia Neves Garcia; Karolyn Sales Fioravanti; Karin Hermana Neppelenbroek; Thaís Marchini Oliveira; Chiarella Sforza; Simone Soares (Sociedade Brasileira de Pesquisa Odontológica, 2024)
Abstract: This cross-sectional observational study aimed to evaluate and compare facial metrics in women aged 20-65 years using a three-dimensional (3D) stereophotogrammetry system and to establish standardized values for facial metric variations in different age subgroups. This study included 84 Caucasian women divided into two groups based on their age: group 1 (G1) included women aged 20-40 years and group 2 (G2) included women aged 41-65 years. Twenty-one morphometric points on the face were identified, and the facial images were captured using a 3D stereophotogrammetry system, Twenty-three linear measures and 12 angular measures were evaluated, revealing statistically significant differences in 11 linear and 5 angular measures between the groups. In the G2 group, nasal and mouth width, lip philtrum height, Tragus-Nasion and Tragus-Pronasale lengths were increased, along with increased nasofrontal angle, decreased palpebral fissure inclination, and lip vermilion angles. However, palpebral fissure width and height, binocular width, and lip vermilion height were reduced. The aging process in women causes substantial changes in facial features, particularly in the middle and lower thirds of the face. Conversely, no major changes were observed in the upper third of the face. Our study findings provide potential insights for clinicians in developing facial rejuvenation procedures as well as for forensic purposes and surgical planning. The standardized facial metrics values in different age subgroups can guide clinicians in determining appropriate treatment plans for patients seeking facial rejuvenation.